Women’s and Health Officer’s Knowledge on Access to Reproductive and Sexual Health Services Covered by the National Health Insurance: Surveys in 15 Districts-Cities in Indonesia - Herna Lestari; Atnike Nova Sigiro (Yayasan Jurnal Perempuan, 2019)
The availability of reproductive and sexual health services provided by the National Health Insurance (Jaminan Kesehatan National/JKN) in Indonesia could expand women’s access to reproductive and sexual health services. However, the knowledge of community and service provider will determine to what extent women will access the reproductive and sexual health services provided by JKN. This article assesses and analyzes the knowledge of women and health officers about the availability of reproductive and sexual health services provided in JKN. The article elaborates for main findings from the research that was conducted by women organizations that are members of the Women’s Health Care Network (Jaringan Perempuan Peduli Kesehatan or JP2K). JP2K conducted longitudinal research with a series of surveys in 2015, 2016, and 2017 in 15 regions of districts/cities in Indonesia on knowledge and access to reproductive and sexual health services provided by JKN. The surveys show limited knowledge of the respondents, both women and health officers, about forms and scope of reproductive and sexual health services that are covered by JKN. The research concludes that one of the important agendas for encouraging women’s access to health services covered by JKN is through intensifying the socialization of the scope of sexual and reproductive health to women and health facility officers.